2019
DOI: 10.1177/1368430219869460
|View full text |Cite
|
Sign up to set email alerts
|

Who is most influential? Adolescents’ intergroup attitudes and peer influence within a social network

Abstract: Research has shown that adolescents’ intergroup attitudes are subject to friends’ influence, but it remains unknown if certain friends are more influential than others. Popular adolescents may be especially influential of their friends’ intergroup attitudes because they can set peer norms. We examined several indicators of popularity in social networks as possible determinants of social influence: sociometric popularity, prestige popularity, being a clique leader, and frequency of contact with friends. Longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 98 publications
0
29
0
Order By: Relevance
“…There is much recent research on what might be called network-based approaches to social influence, whereby influence arises from one's position in social networks and interactions with others in the network form the channels of social influence (e.g., Leszczensky et al 2019, Zingora et al 2020. For example, in a study of student networks, Zingora et al (2020) found that interpersonal bonds channelled influence on intergroup attitudes, with popular students having greater influence. The relation to group identity is often implicit in this literature, arguably because the focus is on interpersonal bonds and interactions rather than group identity (see Postmes et al 2005).…”
Section: Group Influence Without Group Identity: Interdependence Individual Interest and Impression Managementmentioning
confidence: 99%
“…There is much recent research on what might be called network-based approaches to social influence, whereby influence arises from one's position in social networks and interactions with others in the network form the channels of social influence (e.g., Leszczensky et al 2019, Zingora et al 2020. For example, in a study of student networks, Zingora et al (2020) found that interpersonal bonds channelled influence on intergroup attitudes, with popular students having greater influence. The relation to group identity is often implicit in this literature, arguably because the focus is on interpersonal bonds and interactions rather than group identity (see Postmes et al 2005).…”
Section: Group Influence Without Group Identity: Interdependence Individual Interest and Impression Managementmentioning
confidence: 99%
“…Despite an increasing interest in understanding the factors that might play a role in why some people are open to diversity whereas others are not, there are two main limitations of the current literature. First , the available studies mostly focus on young adults, namely university students; not much is known about how young people approach diverse perspectives during their adolescence, except from studies examining adolescents’ intergroup relationships (Rivas‐Drake et al 2019 ) and attitudes toward immigrants (van Zalk and Kerr 2014 ; Zingora et al 2020 ). Critical cognitive and social changes occur during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting these arguments, research has shown that peers may serve as socializing agents in the formation and continuation of intergroup relations (Tropp et al 2016 ). That is, the peers whom adolescents interact with—and these people’s views on out-group members—may influence what adolescents think about out-group members (Rivas‐Drake et al 2019 ; van Zalk et al 2013 ; Zingora et al 2020 ) and how they interact with them (Titzmann et al 2015 ; Tropp et al 2016 ). For example, recent studies have shown that adolescents become more tolerant over time (van Zalk and Kerr 2014 ), or develop a positive orientation toward intergroup relations (Rivas‐Drake et al 2019 ; Zingora et al 2020 ), when they themselves have friends with positive views on intergroup relations.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, individuals targeted within a network for an intervention are those most likely to have the greatest and widest influence on others in the network. In line with this reasoning, research to date provides an initial indication that interventions should target popular members of the majority group (Bracegirdle et al, under review;Zingora et al, 2020). Few studies have implemented network interventions improving intergroup relations.…”
Section: Longitudinal Social Network Analysismentioning
confidence: 99%